Advances in endotherapy in chronic pancreatitis - Emmanuel Coronel; Tomas DaVee; Jeffrey H. Lee (Gastrointestinal Intervention, 2017)
Patients with chronic pancreatitis may develop complications such as chronic debilitating abdominal pain related to neuropathy, pancreatic duct leaks, pseudocysts, pancreatic carcinoma, pancreatic duct calcifications and strictures. Management of mechanical complications of chronic pancreatitis may pose a significant challenge to the interventional endoscopist. The purpose of this manuscript is to explore the latest developments in interventional techniques and to set the stage for future investigations.